The 2013 International Joint Conference on Neural Networks (IJCNN) 2013
DOI: 10.1109/ijcnn.2013.6706962
|View full text |Cite
|
Sign up to set email alerts
|

Spike-based learning of transfer functions with the SpiNNaker neuromimetic simulator

Abstract: Recent papers have shown the possibility to implement large scale neural network models that perform complex algorithms in a biologically realistic way. However, such models have been simulated on architectures unable to perform realtime simulations. In previous work we presented the possibility to simulate simple models in real-time on the SpiNNaker neuromimetic architecture. However, such models were "static": the algorithm performed was defined at design-time. In this paper we present a novel learning rule,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, such models were "static", the algorithm performed was defined at design time. In 2013 a paper [174] was published, in which a novel learning rule was presented, describing its implementation into the SpiNNaker system, which enables models designed with the NEF to learn the function to be performed using a supervised framework. The authors showed that the proposed learning rule, belonging to the Prescribed Error Sensitivity class, is able to learn effectively both linear and non-linear function.…”
Section: Spinnakermentioning
confidence: 99%
“…However, such models were "static", the algorithm performed was defined at design time. In 2013 a paper [174] was published, in which a novel learning rule was presented, describing its implementation into the SpiNNaker system, which enables models designed with the NEF to learn the function to be performed using a supervised framework. The authors showed that the proposed learning rule, belonging to the Prescribed Error Sensitivity class, is able to learn effectively both linear and non-linear function.…”
Section: Spinnakermentioning
confidence: 99%
“…The SpiNNaker was created simulate real-time models, but the algorithms had to be defined in the design process, therefore the models were static. In 2013, a paper [ 109 ] was published, in which a novel learning rule was presented, describing its implementation into the SpiNNaker system, which allows the use of the Neural Engineering Framework to establish a supervised framework to learn both linear and non-linear functions. The learning rule belongs to the Prescribed Error Sensitivity class.…”
Section: Neuromorphic Chipsmentioning
confidence: 99%